Evaluation of high temperature oxidation performance of bare and coated T91 steel. (2020) - Kumar, Manoj; Mudgal, Deepa; Ahuja, Lalit
Abstract: Ferritic stainless steel is widely used in construction of boiler components. However due to very high temperature in boiler, the material used for construction suffered from corrosion. Thermal spray techniques are commercially used to deposit coatings on the materials specifically used for high temperature. Hence, in the present study bare, WC-CO and Cr3 C2 -NiCr coated T91 steel substrates were tested in laboratory to check it sustainability at 800 °C. The coatings were deposited using D-gun technique. The experiments were carried out in laboratory tubular furnace under cyclic condition. The results show that WC-Co coating was delaminated from the substrate whereas Cr3 C2 -NiCr coating remains adhere to the substrate even after 50 cycles of oxidation.